Defense, peace, and war economics - Coyne, Christopher J. (Cambridge : Cambridge University Press, 2020)
This Element surveys the field of defense, peace, and war economics with particular emphasis on the contributions made by Austrian economists. I first review treatments of defense, peace, and war by the classical economists. I then discuss the rise of a distinct and systematic defense, peace, and war economics field of study starting in the 1960s. Next, I consider the contributions by Austrian economists to the field. This includes the economic analysis of the nature of the war economy, problems with the public good justification for the state provision of defense, the seen and unseen costs of war, the idea of the liberal peace, and the realities and limitations of foreign intervention. I conclude with a discussion of some open areas for future research.
Title from publisher's bibliographic system (viewed on 28 Feb 2020).
Keywords: War -- Economic aspects; Austrian school of economics